Influence of plant development stage on carbohydrate composition of stems and leaves of pineapple - Dea de Carvalho, Vânia; Chalfoun, Sara Maria; Steiner Gomes Juste Junior, Eufêmio; Maia, Aloísio (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of selecting better periods of pineapple plant (Ananas comosus L.) development for obtaining stems and leaves with the highest carbohydrate content, the weights of stems and leaves, as well as their starch and total sugar contents derived from plants obtained from nursery slips or from traditional cuttings and harvested at the flowering, green fruit, mature fruit stages and at two and four-month after fruit harvest, were determined. It was concluded that: a) the stems presented greater yields of starch and total sugars at two and four months, and leaves at four months after fruit harvest; b) the starch and total sugar contents of the stems and leaves decreased in the period corresponding to fruit ripening, and increased to maximum levels at two and four months after fruit removal and, of the tendencies of variations in starch and total sugar contents were similar in stems and leaves derived from traditional cuttings and from nursery slips.